Big city Bombus: using natural history and land-use history to find significant environmental drivers in bumble-bee declines in urban development. Issue 5 (17th May 2017) - Glaum, Paul; Simao, Maria-Carolina; Vaidya, Chatura; Fitch, Gordon; Iulinao, Benjamin
Abstract : Native bee populations are critical sources of pollination. Unfortunately, native bees are declining in abundance and diversity. Much of this decline comes from human land-use change. While the effects of large-scale agriculture on native bees are relatively well understood, the effects of urban development are less clear. Understanding urbanity's effect on native bees requires consideration of specific characteristics of both particular bee species and their urban landscape. We surveyed bumble-bee ( Bombus spp.) abundance and diversity in gardens across multiple urban centres in southeastern Michigan. There are significant declines in Bombus abundance and diversity associated with urban development when measured on scales in-line with Bombus flight ability. These declines are entirely driven by declines in females; males showed no response to urbanization. We hypothesize that this is owing to differing foraging strategies between the sexes, and it suggests reduced Bombus colony density in more urban areas. While urbanity reduced Bombus prevalence, results in Detroit imply that 'shrinking cities' potentially offer unique urban paradigms that must be considered when studying wild bee ecology. Results show previously unidentified differences in the effects of urbanity on female and male bumble-bee populations and suggest that urban landscapes can be managed to support native bee conservation.